Rare giant retroperitoneal melanotic schwannoma: a case report and literature review - Chen, Pan; Cheng, Junfeng (Frontiers in Oncology, 2024)
BackgroundMelanotic schwannoma (MS), a rare variant of peripheral nerve sheath tumor, is especially infrequent when originating from the peritoneum. Its definitive diagnosis relies on postoperative histopathological examination and immunohistochemical analysis, while preoperative diagnosis is difficult.Case presentationIn the present study, we reported a rare case of giant MS in the retroperitoneum, which was previously misdiagnosed before surgery. However, intraoperative exploration revealed it was retroperitoneal tumor. The tumor had invaded the abdominal aorta and bilateral common illiac artery walls. A surgical resection was subsequently executed, and postoperative histopathological examination confirmed it as a MS.ConclusionThe incidence of peritoneal MS is extremely rare, and surgical resection remains the preferred treatment modality. Given the absence of established guidelines for postoperative adjuvant therapy, long-term follow-up becomes imperative to accumulate valuable clinical expertise.